The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1590/s0103-84782008000300022
|View full text |Cite
|
Sign up to set email alerts
|

Estimulação elétrica neuromuscular de média freqüência (russa) em cães com atrofia muscular induzida

Abstract: III Medium frequency neuromuscular electrical stimulation (russian) in dogs with induced muscle atrophy RESUMO A estimulação elétrica neuromuscular (EENM) de média freqüência (Russa) ou de ABSTRACT The medium frequency neuromuscular electrical stimulation (NMES) (Russa) or Kotz is designed for recuperation of muscle mass in dogs with muscular atrophy in disuse. This study aims to utilize medium frequency NMES on the femoral quadriceps of dogs with induced muscular atrophy and evaluate the occurrence of gain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…Pelizzari et al 12 conducted a study with eight dogs where they proposed to observe the effect of NMES on induced atrophy of the quadriceps, and at the end of the study observed that NMES associated with activities provides an increase in muscle mass in dogs with induced muscular atrophy. In a study conducted with 20 soccer players, by Billot et al ., 27 they ascertained that the electrical stimulation of the quadriceps associated with training (isometric, concentric and eccentric), results in better muscle strength, a better concentric torque and a better kicking speed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelizzari et al 12 conducted a study with eight dogs where they proposed to observe the effect of NMES on induced atrophy of the quadriceps, and at the end of the study observed that NMES associated with activities provides an increase in muscle mass in dogs with induced muscular atrophy. In a study conducted with 20 soccer players, by Billot et al ., 27 they ascertained that the electrical stimulation of the quadriceps associated with training (isometric, concentric and eccentric), results in better muscle strength, a better concentric torque and a better kicking speed.…”
Section: Discussionmentioning
confidence: 99%
“…- 10 Bril et al 11 in his study with 15 healthy patients of both sexes, achieved gains of muscle strength and trophism by associating "Russian stimulation" with resistance exercises. A study carried out by Pelizzari et al 12 demonstrated that the use of medium-frequency neuromuscular electrical stimulation (NMES) produced an increase in muscle mass in a dog with induced muscular atrophy. In a study conducted by Modli el al 13 ,.…”
Section: Introductionmentioning
confidence: 99%
“…A goniometria da articulação femorotibiopatelar observada nos cães apresentaram resultados (Figura 2) semelhantes aos encontrado em outro estudo [14] que relataram diminuição da amplitude articular aos 30 dias de PO e aumento aos 60 dias da cirurgia. Em um trabalho [18] verificaram que os animais submetidos à terapia física atingiram os valores da goniometria iguais aos mensurados no pré-operatório, decorridos 90 dias de PO.…”
Section: Discussionunclassified
“…O protocolo fisioterapêutico realizado no Fisiovet (Quadro 1) iniciou com a massagem, MPA e reflexo flexor dos MP, executadas como mencionado anteriormente; alongamento em extensão e flexão; MPA de cada articulação dos MP; estimulação elétrica neuromuscular (EENM) de média frequência (Russa) sobre os músculos da coxa, conforme recomendações de Pelizzari et al (2008).…”
Section: Methodsunclassified